Risk factors for persistent airflow limitation: Analysis of 306 patients with asthma - Wang, Lingcheng (Pak J Med Sci, 2014)
Objectives : To determine the risk factors associated with persistent airflow limitation in patients with asthma. Method s: This study was designed and carried out in the department of respiratory medicine, fourth People’s Hospital of Jinan City, Shandong province, China between Jan 2012 and Dec 2012. Three hundred and six asthma patients participating in the study were divided into persistent airflow limitation group (PAFL) and no persistent airflow limitation group (NPAFL). The patients participated in pulmonary function tests and sputum induction examination. The clinical data including age, gender, onset age, disease course, smoking history, family history, regular corticosteroid inhalation, hospitalization history and presence of atopy were collected. Results : In 306 patients, 128 (40.5%) were included in PAFL group and 178(59.5%) in NPAFL group. Multivariate analysis demonstrated smoking (≥10 pack-years; OR, 7.1; 95% CI, 1.8 to 31.2), longer asthma duration (≥ 20years) (OR, 6.3; 95% CI, 1.7 to 28.5), absence of regular corticosteroid inhalation (OR, 3.5; 95% CI, 1.1 to 14.5) and neutrophil in induced sputum≥65% (OR, 1.8; 95% CI, 1.0 to 2.8) were independent risk factors for PAFL. Conclusions : Smoking, longer asthma duration and increased neutrophil in induced sputum are risk factors for PAFL, while regular corticosteroid inhalation is protective factor. Smoking cessation and regular corticosteroid inhalation may play an important role in preventing the occurrence of persistent airflow limitation group (PAFL).